155: Impact of the Pediatric Residents' Initiative for Healthy Active Living in Youth (RHALY): A Prospective Cohort Study. Issue 6 (1st June 2014) - Al Khalifah, RA; Mok, E; Legault, L; Desrochers, J; Le Blanc, C; Constantin, E
Abstract: BACKGROUND: Suboptimal lifestyle habits may lead to childhood overweight and obesity. Promotion of healthy active living (HAL) is an important part of clinical practice. To promote healthy lifestyle in youth, we created a resident-led HAL educational program (including a HAL counselling intervention) at the Montreal Children's Hospital. OBJECTIVES: To determine the prevalence of optimal health habits in children followed in our Pediatric Residents Continuity Clinic (RCC); To examine the effect of our HAL counselling intervention on the health habits of these children. DESIGN/METHODS: This prospective cohort included five to 16 year-old children. Our HAL educational program included 1) didactic teaching sessions on childhood obesity screening and management incorporated within the residents teaching curriculum; and 2) creation of HAL counselling tools (brochures, pamphlets, and healthy habits prescription). Pediatric residents implemented the HAL counseling intervention to patients/families using the 5, 2, 1, 0 guidelines (four daily goals: five portions of fruits/vegetables; <2 h screen time; >1 hr physical activity, zero sugar-sweetened beverages); and HAL counselling tools. Recruited patients and families completed a questionnaire reporting their health habits at baseline, six months and one year following the intervention. RESULTS: We recruited 81 patients (9.3±3.1 years old; 48% females). 20% of our cohort was overweight or obese. 19% reported optimal healthy habits (i.e., met all four goals). There was an increase in the proportion of children who met three or four goals following our intervention (49% vs 64% at follow-up), P=0.035. Among overweight/obese children, the improvement was from 33% at baseline to 56% at 12 months follow-up; in non-obese children, 51% to 63%. Specifically, changes for each met goal by category from baseline compared to 12 months were: five portions of fruits/vegetables, 32% vs 49%; <2 h screen time, 58% vs 69%; >1 h physical activity, 48% vs 67%; no sugar-sweetened beverages, 44% vs 58% (P value for each goal was non-significant) The mean activity level increased by 18 min/day (75.5±53.2 vs 93.6±65.2 at follow-up), and sleep duration increased by 25 min (10.0±1.4 h vs 10.4±1.2 h), but neither reached statistical significance (P=0.074 and 0.060, respectively). CONCLUSIONS: We were able to show for the first time that using a HAL counselling tool in a primary clinical care setting led to a significant increase in the proportion of children meeting 5, 2, 1, 0 guidelines after the intervention, as well as clinically important increases in physical activity level and sleep duration. Future studies are needed to validate our findings.